The clinical method as a teaching method in the Medical Career - Luis Allberto Corona Martinez; Mercedes Fonseca Hernández (Medisur)
The clinical method applied in the medical assistance to sick people is an essential category in the Clinical Sciences. Its use as a method in the teaching learning process in the disciplines and subjects of the clinical cycle in the medical profession contributes not only to master this method deeply, but to systematize all those abilities, that as a system, gather as a whole during its application. Therefore, the clinical method constitutes the main via to develop the student’s professional abilities, proving that the logic of the profession becomes at the same time the logical thinking of the Comprehensive General Doctor’s formative process. This paper’s main purpose is to consider the clinical method as the teaching method for teaching, learning and developing the doctors’ professional abilities .